Yıldırım Akbulut Hükümeti (1989-1991) - Ataş, Erşan (My University, 2019)
Bu çalışmada 1983 yılı sonunda Türkiye’de iktidara gelen 8 yıllık ANAP Hükümeti’nin üçüncü hükümeti olarak kabul edilen Yıldırım Akbulut Hükümeti’nin (1989-1991) siyasi, ekonomik ve sosyo-kültürel icraatları ele alınmıştır

In this study by the end of 1983, 8-year ANAP government came to power in Turkey, known as the third government adopted Yildirim Akbulut Government (19891991) political, economic and socio-cultural acts are dealt with.
Keywords: Anap; Politics and government; Siyaset ve yönetim; Turgut Özal; Turkey; Türkiye; Yıldırım Akbulut; Yıldırım Akbulut Anap; Yıldırım Akbulut, 1935-